2018
DOI: 10.1159/000494332
|View full text |Cite
|
Sign up to set email alerts
|

The State of Nutrigenomic Education in Poland

Abstract: Background: In Poland, 45 higher education institutions offer degrees in dietetics. However, only 20 of these offer nutrigenomics or nutrigenetics courses. Objectives: The purpose of this study was to assess the current state of nutri­genomic education in Poland and to evaluate the level of nutrigenomic knowledge held by dieticians. Methods: A cross-sectional survey was performed to examine the self-reported attitudes of 193 dietetics students and dietetics professionals who graduated from 33 Polish higher-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A need for NGT training materials is evident, and while NGT companies can be a valuable source, additional efforts are needed from other sources. It is important to note that a subset of HCPs in our investigation accessed training from a professional organization’s nutrigenomics online course, which is a format that can be further developed [33] along with increasing availability of nutrigenomics courses in HCP education [34, 35]. Moreover, our findings indicate that patients are more likely to approach an HCP when they have an existing interest in NGT as opposed to an HCP initially recommending a test.…”
Section: Discussionmentioning
confidence: 99%
“…A need for NGT training materials is evident, and while NGT companies can be a valuable source, additional efforts are needed from other sources. It is important to note that a subset of HCPs in our investigation accessed training from a professional organization’s nutrigenomics online course, which is a format that can be further developed [33] along with increasing availability of nutrigenomics courses in HCP education [34, 35]. Moreover, our findings indicate that patients are more likely to approach an HCP when they have an existing interest in NGT as opposed to an HCP initially recommending a test.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of several articles directly relevant to the dietetics community from around the world revealed that these articles continue to use the term nutrigenomics to describe the use of genetic variations to personalize dietary recommendations. [2][3][4][5][6][7][8][9][10][11][12] The use of the term nutrigenomics is similarly used by various regulatory bodies and dietetic organizations globally. [13][14][15][16][17] Importantly, to avoid potential confusion, we indicated in the introduction of the article that "the term nutrigenomics is used to describe the application of genetic information to personalize nutrition recommendations."…”
Section: Authors' Responsementioning
confidence: 99%